Identity in Persian Egypt: the fate of the Yehudite community of Elephantine - Becking, Bob (Penn State University Press, 2021)
Frontmatter -- Table of Contents -- Introduction -- List of Abbreviations -- Chapter 1. How Persian Power Entered Egypt -- Chapter 2. Yehudites at Elephantine: Provenance, Identity, and Religion -- Chapter 3. Multiethnic Elephantine: Some Remarks on Different Minor Ethnicities in a Persian Border Garrison -- Chapter 4. Pax Persica: Cooperation, Cohabitation, and Acceptance -- Chapter 5. Control Through Education, Law, and Military Power -- Chapter 6. Disruptions of the Interethnic Solidarity -- Chapter 7. “Khnum Is Against Us Since Hananiah Has Been in Egypt”: On Two Historical Movements in the Fifth Century BCE -- Chapter 8. Beyond the Final Curtain: The Aftermath of Elephantine -- Bibliography -- Index of Authors -- Index of Ancient Sources